Heavy metal detoxification by recombinant ferritin from Apostichopus japonicus. Issue 66 (30th August 2017) - Si, Kaixue; Ming, Tinghong; Li, Yanyan; Qiu, Xiaoting; Chen, Liping; Zhou, Jun; Lu, Chenyang; Su, Xiurong; Li, Ye; Cheong, Ling-Zhi
Abstract : Ferritin from Apostichopus japonicas showed better ability in heavy metal detoxification than horse spleen ferritin. Abstract : Ferritin is a bionanomaterial that is widely applied in magnetic resonance imaging, drug delivery systems, biocompatible fluorescence, neutron-capture therapy and electrochemical markers. Ferritin also has great potential for use in environmental detection and heavy metal removal due to its hollow cage sequestration and maintenance of iron in a nontoxic and bio-available form. In this study, the heavy metal binding activity of ferritin from Apostichopus japonicus (AjFER) was elucidated using scanning electron microscopy (SEM). It was observed that ferritin aggregation morphology changed dramatically upon exposure to five metals. The reaction systems formed ferritin-Cd, ferritin-As, ferritin-Hg, ferritin-Pb, and ferritin-Cr aggregations. The aggregations of horse spleen ferritin (HSF) and AjFER are relatively unified rules. The enrichment capacity of ferritin was further analyzed using Inductively Coupled Plasma Mass spectrometry. The contents of Cd 2+, Hg 2+, Cr 3+, Pb 2+, and As 3+ enriched by recombinant AjFER were higher than that for the standard HSF in ordinary groups. Moreover, the concentration levels of enriched heavy metal ions in groups treated with phosphate were higher than those in ordinary dialysis control AjFER groups. The conformation stability of AjFER binding to different heavy metal ions was determined using Circular Dichroism (CD) spectroscopy, which revealed that the second structure of M n + -ferritin has relative stability. The affinity of ferritin for metal ions was determined using Isothermal Titration Calorimetry (ITC), and the order of binding constant was Pb-Fer > Hg-Fer > Cd-Fer > As-Fer > Cr-Fer. The ion channel was measured using site-directed mutagenesis, which revealed that heavy metal ions primarily enter the protein cage via a three-fold channel and that the ferroxidase center may be one of the key sites for metal ion diffusion into the interior of the protein shell.